(010) facets dominated LiFePO4 nano-flakes confined in 3D porous graphene network as a high-performance Li-ion battery cathode. Issue 15 (15th October 2018) - Yi, Xu; Zhang, Fuqin; Zhang, Bao; Yu, Wan-Jing; Dai, Qiongyu; Hu, Shengyong; He, Wenjie; Tong, Hui; Zheng, Junchao; Liao, Jiqiao
Abstract: Olivine-structured LiFePO4 (LFP) has been widely considered as one of the most promising and safest high-power positive electrode materials for lithium-ion batteries (LIBs) as a power source in the electric transportation. However, the electrochemical behavior of LFP for lithium-storage is seriously restrained by its intrinsic feature of low electrical conductivity and poor lithium-ion diffusion ability. In this research, LFP nano-flakes with oriented (010) facets were prepared through the solvothermal method, and 3D porous composite of LFP nano-flakes confined on graphene (LFP@G) was synthesized by freeze-drying concentrated graphene-oxide-gel containing LFP nano-flakes followed by a heat-treatment process. As the cathode materials for LIBs, LFP@G composite can release a reversible specific capacity of 129 mAh g −1 at a high current rate of 20 C. Meanwhile, a long cycling stability for LFP@G composite with a capacity of 139.8 mAh g −1 over 600 cycles up to 10 C can be achieved. The superior electrochemical Li-storage properties of LFP@G composite can be ascribed to the fast lithium-ion transfer channels of LFP originated from the exposed (010) planes, shortened lithium-ion diffusion distance, and the excellent two-phase electric contact between LFP and graphene in the 3D porous graphene conductive network for fast electron and lithium-ion transport.